Post-colonial Criminality in John Kiriamiti’s My Life in Crime - Meriem MERZOUGUI . Alia LATRACH, Ms. Amel BENIA (université mohamed boudiaf .m'sila, 2023)
Abstract Crime is one of the most common problems in the modern world, and its complexity intensifies when it emerges in post-colonial societies. Consequently, this dissertation examines crime-related issues in African countries that experienced European colonization through crime fiction representations, with Kenya serving as a case study. It aims to provide a comprehensive understanding of Kenyan crime fiction's engagement with post-colonial challenges, shedding light on its impact on society's perceptions of crime and criminals. Through an analysis of John Kiriamiti’s autobiography My Life in Crime, the study examines how the book tackles the issue of crime present during the post-colonial era and attributes it to the legacy of colonialism. Moreover, it discusses the depiction of the capital Nairobi as a city plagued with crime where the youth are pushed into a life of crime because of the colonial legacy. Furthermore, the research delves into the moral dilemmas surrounding criminal confession in literature and questions its reliability and purpose through an exploration of the author’s narrative techniques, as well as the definitions of guilt such as that of Freud’s. It also investigates the portrayal of criminals as heroic figures, delving into the motivations that drive authors to employ this narrative device and the readers’ tendency to sympathize with such characters. In order to achieve this, the research provides a comprehensive historical and critical account of Kenya’s colonial background in addition to an examination of the colonial and neocolonial legacies. Additionally, it relies on Edward Said’s insights on neocolonialism and the consequences of Imperialism on post-colonial countries, as well as certain theories of criminology, in order to analyze Kiriamiti’s autobiography.
Keywords: Key words: colonial legacy, crime, crime fiction, post-colonialism, neocolonialism, confession, autobiography